Evidence for saprotrophic digestion of glossopterid pollen from Permian silicified peats of Antarctica - McLoughlin, Stephen; Shevchuk, Olena; Windell, Megan M.; Slater, Ben J. (Grana, 2024)
Wind-blown pollen (pollen rain) is a major contributor to element cycling in modern forests and aquatic ecosystems, particularly in high-latitude and acidic settings where nutrients are a limiting factor. The rich package of proteins, nitrogen and phosphorus residing within pollen is, nonetheless, inaccessible to most organisms, owing to the indigestible sporopollenin walls. Saprotrophic breakdown by fungi, and some non-fungal microorganisms, can make nutrients bioavailable, and represents a key trophic link in element cycling and the transfer of organic carbon. Little is known about when micro-saprotrophs first adapted to exploit pollen, thus establishing this crucial step in the evolution of modern terrestrial ecosystems. One approach is to examine the rich fossil record of palynomorphs. Here we describe translucent bodies referable either to fungi (Chytridiomycota) or water moulds (Oomycetes) within the pollen of glossopterid gymnosperms and cordaitaleans, and fern spores from silicified Permian (Guadalupian–Lopingian) peats of the Toploje Member, Bainmedart Coal Measures, Prince Charles Mountains, Antarctica. These probable holocarpic thalli or oospores exploited the nutrient-rich microgametophyte tissue of dispersed miospores in high-palaeolatitude wetlands. The exceptional preservation of fossil microorganisms in permineralised peats offers insights into the deep-time evolution of intimate ecological relationships, otherwise known only among extant biotas. Permineralisation has preserved sub-micron details of these delicate and cryptic saprotrophs that likely played key roles in cycling nutrients in the acidic forest mires of the Permian. Our study reveals that the extensive recapture of spore/pollen-derived nutrients via saprotrophic digestion was already at play in the high-latitude ecosystems of the late Palaeozoic. This work was supported by Swedish Foundation for Strategic Research (SSF) individual research grant: [Grant Number O. Shevchuk 2022–2024]; Vetenskapsrådet: [Grant Numbers 2020-03314 and ...